EFEKTIFITAS STRATEGI ??PAKET? BERBASIS MULTIMEDIA DALAM KEMASAN CD INTERAKTIF PADA PEMBELAJARAN MATEMATIKA MATERI GEOMETRI SISWA KELAS VII - LILIK SULISTYO (Jurnal DISPROTEK, 2014)
ABSTRACT A new system of learning activity emerged due to the conventional learning activity system was considered not as effective and efficient in learning activity process. Then, many educators conducted research to find a new concept of learning to increase learning quality in classroom, and to find a new strategy of learning in order to be more effective. Learning process is not only of how to transfer knowledge but also how students interacted actively with media and learning environment to construct knowledge need. The fundamental strategy to enhance learning activity in classroom is the strategy in a ?package? of multimedia as base Interactive CD. This research aims to know: (1) the effect of skill students processed in mathematics learning with PAKET as a base multimedia in CD interactive package toward learning result. (2) which more effective between skill students processed in mathematics learning with PAKET as a base multimedia in CD interactive package toward learning result and mathematics learning used expository strategy with LKS and visual aid. (3) the difference of learning result between group of students in high, medium, and low in learning process used strategy of PAKET as a base multimedia in CD interactive package with a conventional learning process. This research is experiment study in SMP Siswa Utama Semarang that consisted of 5 classes by taking one class of experiment with mathematics learning used PAKET strategy as a base multimedia in CD interactive package with a conventional learning process and another class control with learning strategy of expository used LKS and visual aid. The research data was captured through: (1) observation sheet, (2) cognitif skill test, and (3) questionnaire. The effect would be identified by regression analysis test, in addition to identify whether there was the difference used by One Way Anova then continued with continuous test NAVA with Scheffe method, and t test was used for knowing better test. The result showed that: (1) regression test result with signification score 0,00 < 5%, showed there was an effect of skill process toward students learning result in experiment class. From the table of Summary model could be captured that R square score is 0,578. It means skill process give an effect to the goal of students learning 57,8 %. (2) the result of t test with significant score is 0,00 < 5 %, showed that learning in experiment class gave process skill in amount of 78,14 better than in control learning class 70, 26. (3) One Way Anova with a significant score was 0,00 < 0,05 = 5 % showed there was a difference of learning result between students in a group of high medium low in experiment learning class. In other words, if it was compared with control class, the analysis result showed that strategy of PAKET could increase learning result to all students group. (4) t test result with significant score in amount of 0,003 < 0,05 = 5 % showed that learning in experiment class gave an average score in amount of 69,4318 with classical success in amount of 86,4 % better than learning in control class. Keywords: PAKET, learning activity process, new strategy of learning, learning strategy, CD interactive. ABSTRAK Munculnya gagasan baru dalam pembelajaran disebabkan ketidakpuasan terhadap sistem pembelajaran lama yang dianggap kurang efaktif dan efisien. Kemudian bermunculan penelitian pembelajaran dalam upaya meningkatkan kualitas pembelajaran, serta penggunaan strategi pembelajaran yang lebih efektif. Proses belajar tidak lagi dipandang sebagai proses transfer pengetahuan saja. Belajar dipandang sebagai proses interaksi aktif siswa dengan media dan lingkungan belajar untuk mengkonstruk pengetahuan yang dibutuhkan. Salah satu strategi pembelajaran yang diharapkan mampu memenuhi kebutuhan tersebut adalah strategi ?PAKET? berbasis multimedia dalam kemasan CD Interaktif. Penelitian ini bertujuan untuk mengetahui : (1) pengaruh keterampilan berproses siswa dalam pembelajaran matematika dengan menggunakan strategi PAKET berbasis multimedia dalam kemasan CD interaktif terhadap hasil belajar. (2) manakah yang lebih baik antara keterampilan berproses siswa dalam pembelajaran matematika dengan menggunakan strategi PAKET berbasis multimedia dalam kemasan CD interaktif dengan keterampilan proses siswa dalam pembelajaran matematika menggunakan strategi ekspositori menggunakan LKS dan Alat Peraga. (3) perbedaan hasil belajar antara siswa pada kelompok atas menengah dan bawah pada pembelajaran menggunakan strategi PAKET berbasis multimedia dalam kemasan CD interaktif, dan (4) manakah yang lebih baik antara pembelajaran menggunakan strategi PAKET berbasis multimedia dalam kemasan CD interaktif dengan pembelajaran konvensional. Kata Kunci : PAKET, Proses pembelajaran, strategi pembelajaran terbaru, strategi pembelajaran, CD interaktif